Kontribusi Locus Of Control Terhadap perilaku Kecemasan Berkomputer Mahasiswa Akuntansi Universitas Muhammadiyah Jember Dalam Menggunakan Software Akuntansi - Rendy Mirwan Aspirandi; Diyah Probowulan; Aldi Putra Fajariyanto (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The purpose of this study was to determine the contribution of locus of control and personality type to accounting students' computer anxiety in using accounting software. The population in this study were students majoring in accounting class 2018 Muhammadiyah University of Jember. The research method uses a quantitative survey, the sampling technique in this study is stratified random sampling, based on this technique 60 active students who meet the requirements as an example. The results showed that locus of control and personality type had a positive effect on accounting students' computer anxiety in using accounting software.